2018
DOI: 10.1111/ijn.12644
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for multidrug‐resistant Gram‐negative bacteria infection in intensive care units: A meta‐analysis

Abstract: Six risk factors were associated with multidrug-resistant Gram-negative bacterial infection in intensive care units. Antimicrobial stewardship, infection control, and medical staff prevention care are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 46 publications
(126 reference statements)
3
19
1
Order By: Relevance
“…For antibiotic treatment, the present study found that prior antibiotic treatment was a significant risk factor for MDR bacterial infection in LRTIs. This finding is similar to that of the previous studies, which identified the risk factors for MDR PA infection in hospitalized patients [ 44 ] and MDR GNB infection in intensive care units [ 45 ]. The above two systematic reviews could not specify the definitions of previous antibiotic use, nor can they conclude an exact cutoff point for the time frame.…”
Section: Discussionsupporting
confidence: 92%
“…For antibiotic treatment, the present study found that prior antibiotic treatment was a significant risk factor for MDR bacterial infection in LRTIs. This finding is similar to that of the previous studies, which identified the risk factors for MDR PA infection in hospitalized patients [ 44 ] and MDR GNB infection in intensive care units [ 45 ]. The above two systematic reviews could not specify the definitions of previous antibiotic use, nor can they conclude an exact cutoff point for the time frame.…”
Section: Discussionsupporting
confidence: 92%
“…This is because patients who had required MV or undergone tracheotomy can easily be exposed to MDRO colonization 12. ICU admission or broad-spectrum antibiotic use also contributes to MDRO infection,30 and changes to the airway structure are a further risk factor. Meanwhile, in our hospital, the rehabilitation department is famous in Guang Zhou, and there are many patients with tracheotomy coming to that department for rehabilitation treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Case-control studies examining risk factors for isolating Carbapenemase-resistant Enterobacterales (CRE) found recent antimicrobial administration, and carbapenems specifically, to be the largest risk factor [63,64]. Likewise a recent meta-analysis, specifically looking at the risk factors for MDR Gram negative bacteria infection in ICUs, found previous antimicrobial therapy to be key [65].…”
Section: Mechanism: Antimicrobial Resistancementioning
confidence: 99%